EXISTENCE OF INDONESIAN MICRO AND SMALL INDUSTRY PERFORMANCE POST COVID 19 THROUGH DIGITAL ADAPTATION - Rahman, Abdul (Universitas Negeri Makassar, 2025)
Abstract: This study aims to analyze the effect of input usage, e-commerce adoption, inflation rate, and COVID-19 pandemic conditions on the performance of Small and Micro Industries (SMEs) in Indonesia. The research approach used is quantitative using panel data from 34 provinces in Indonesia for the period 2019 to 2023. The analysis model used is panel data regression, with data processing carried out using EViews software. The estimation results show that the input usage variable has a positive and significant effect on SME performance. Meanwhile, the use of e-commerce, inflation rate, and the COVID-19 pandemic dummy variable did not show a significant effect on SME performance during the study period. These findings indicate that optimizing production input remains a key factor in improving SME performance, while digital adaptation through e-commerce still requires capacity building and better infrastructure support to provide real impact. The suggested policy implications include the need for a program to strengthen access to quality production inputs and accelerate SME digital transformation through training, mentoring, and development of a more inclusive e-commerce ecosystem at the regional level.Keywords: MSME Performance, E-Commerce, Inflation, COVID-19